[OA212] A Monte Carlo investigation of dose width product (DWP) as a dose index for CBCT dosimetry. (August 2018) - Abuhaimed, Abdullah; Martin, Colin; Demirkaya, Omer
Abstract : Purpose: Dose-length-product (DLP) plays a vital role in assessing the total energy delivered to patients from CT scans. Moreover, DLP along with conversion coefficients are employed in evaluating effective doses from CT scans. The aim of this study is to propose an alternative dose index for cone-beam CT (CBCT) dosimetry analogue to DLP, which shows limitations for scans acquired with wide beams. Methods: Monte Carlo simulations based on on-board-imager (OBI) kV system were run to investigate the alternative dose index called dose-width-product (DWP), which has a form similar to that of DLP, where width of the scan beam (W) along the z-axis is multiplied by CTDIw . This was proposed for CBCT scans and requires measurement of CTDI100 for a reference beam (≤40 mm) in the standard CTDI PMMA phantoms and measuring CTDI of the reference beam and a wide beam of interest free-in-air. In order to study suitability of DWP, its efficiency was estimated as a ratio of DWP to DWP∞, and compared to DLP/DLP∞ . Head and body phantoms with diameters of 16 and 32 cm, respectively, and a length of 900 mm were simulated to assess DWP∞ and DLP∞, whereas the standard length (150 mm) was used to assess DWP and DLP. The efficiency was estimated using tube potentials of (80, 100, 120, 140) kV and beams of width ranged from 20 – 300 mm. Results: The tube potential and width of the scan beam played a minimal role in the efficiency. Values of DLP efficiency were 80.1 ± 0.5% for head and 72.4 ± 2.4% for body under the different conditions studied. DWP efficiency values for head and body phantoms were all within 1.9% of those for DLP, which gives an indication for suitability of using DWP for CBCT scans. Conclusions: DWP efficiency values were comparable to those for DLP. The dose index DWP is a modified form or an extension to the DLP concept. It indicates possibility of estimation of the total energy resulted from a given CBCT scan with a level of accuracy matching that of DLP. DWP can also be utilized to derive conversion coefficients used to assess effective dose.